Heaven Will Find You (Excerpts) - Lawrence, Sheldon (Dialogue, 2025)
Fiction Editors' Note: As fiction editors at Dialogue: A Journal of Mormon Thought, we're excited to showcase two chapters from Sheldon Lawrence's novel Heaven Will Find You. The novel follows a man who learns that death is no escape from the consequences of a life of broken relationships, self-loathing, and lingering addiction. Though relentlessly pursued and tempted by dark forces in the afterlife, the man also discovers that God is tirelessly in pursuit, too, to remind him of his divine nature. Guided by angels, the man, as he struggles to see himself and others fully through divine eyes, discovers that true righteousness deepens our ability to love and be loved.